Exchange Rate Management and Sectoral Output Performance - Areghan Isibor; Olokoyo Felicia; Arogundade Maria; Osuma Godswill; Ndigwe Chisom (International Journal of Supply Chain Management, 2018)
The goal of every economy is to have a stable exchange rate with the countries it trades with; therefore exchange rate is very vital to the economy of every country. Nigeria has adopted both fixed and fluctuating exchange rate regimes in order to achieve the goal of a realistic exchange rate but this has proven futile as the economy has continued to perform poorly over the years. This study is therefore aimed at examining the effect exchange rate management has on the output performance of both the agricultural sector and the manufacturing sector. Secondary data from 1981 2015 were analyzed using the Ordinary Least Square technique. The results showed that exchange rate has a positive and significant effect on only the agriculture sector. The study recommends amongst others that efforts should be made to increase the exportation of agricultural products in order to boost exchange rate.